2003
DOI: 10.1108/02640470310509135
|View full text |Cite
|
Sign up to set email alerts
|

Internet surfing for the blind: a prototype

Abstract: The right of blind people to access the Internet is simply ignored in many countries because Web pages have been designed for normal people. As a result, many blind people are not enjoying the benefits of the Internet and the improvement in the quality of life that Internet use can bring. In order for visually impaired persons to surf the Internet, it is necessary to develop a special humancomputer interface (HCI) system. This paper presents the design of a Web project for the blind. The aim of this research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…A special software package -VocalSurf (Loo et al, 2003) -originally designed by the author to assist the visually impaired in comprehending web page content through human speech, can also help young children to surf the Internet. This package can read words on web pages and produce human speech accordingly.…”
Section: Software Package Used For the Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A special software package -VocalSurf (Loo et al, 2003) -originally designed by the author to assist the visually impaired in comprehending web page content through human speech, can also help young children to surf the Internet. This package can read words on web pages and produce human speech accordingly.…”
Section: Software Package Used For the Experimentsmentioning
confidence: 99%
“…Further information on this package can be found in the author's previous paper (Loo et al, 2003). In addition to authorizing the 'Hong Kong Blind Union' to distribute the software package to its members, the package has been made available on the website of Hong Kong Education City (http://resources.hkedcity.net/resource_detail.php?rid¼ 955988736).…”
Section: Software Package Used For the Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfred proposed the web prototype for the blind which presented a new human-computer interaction model and an associated computer system for visually impaired people so that they can browse the World Wide web via internet (Loo et al, 2003). Craven and Booth found that, while the aims of the projects differed, the methods adopted were similar including observation, talk aloud protocols, questionnaires, and focus groups.…”
Section: Usability Test Of Library For the Blindmentioning
confidence: 99%
“…In order to facilitate visually impaired users, the screen readers are used in order to reduce their searching time. To facilitate visually impaired users in searching information on internet by developing search engine facility, a desktop application has been introduced which provides speech recognizer and speech synthesizer technology by using audio facility [1]. The main objectives of this research work are:…”
Section: Introductionmentioning
confidence: 99%